Induction infliximab levels among patients with acute severe ulcerative colitis compared with patients with moderately severe ulcerative colitis. Issue 12 (19th April 2016) - Ungar, B.; Mazor, Y.; Weisshof, R.; Yanai, H.; Ron, Y.; Goren, I.; Waizbard, A.; Yavzori, M.; Fudim, E.; Picard, O.; Loebstein, R.; Kopylov, U.; et al.
Summary: Background: Infliximab is effective as salvage therapy for patients with steroid refractory acute severe ulcerative colitis (UC). Although current data suggest that the pharmacokinetics of infliximab are influenced by inflammatory burden in patients with acute severe UC, data comparing infliximab trough levels in patients with acute severe UC vs. moderately severe UC are scarce. Aim: To compare infliximab trough and anti‐infliximab antibody levels at a standard fixed time‐point during induction between patients with acute severe and moderately severe UC. Methods: A multi‐centre retrospective study comparing infliximab drug and antibody levels 14 days after the first infusion in hospitalised acute severe UC versus out‐patients with moderately severe UC was performed. Results: Sixteen acute severe UC patients, hospitalised between 2010–2015 and refractory to intravenous corticosteroids, were treated with infliximab 5 mg/kg salvage therapy. They were compared to 16 moderately severe UC out‐patient controls. Mean infliximab trough levels at day 14 were significantly lower in patients with acute severe UC compared to moderately severe UC (7.15 ± 5.3 vs. 14.4 ± 11.2 μg/mL, P = 0.007). Seven patients (three acute severe and four moderate severe UC) were primary nonresponders to infliximab induction therapy. Infliximab level at day 14 did not differ between responders and nonresponders (9.8 ± 9 vs. 12.1 ± 10.6 μg/mL, respectively, P = N.S.). However, week 2 median antibody‐to‐infliximab levels were numerically higher among primary nonresponders (3.4 ± 5.7 vs. 1.2 ± 4 μg/mL‐eq, respectively, P = 0.06). Conclusions: Infliximab trough levels at day 14 were lower in patients with acute severe UC compared to moderately severe UC, possibly due to a higher inflammatory burden and/or increased drug clearance. However, drug levels at day 14 were not lower among nonresponders compared with responders. Controlled trials are warranted to examine whether an a‐priori‐ intensified infliximab induction protocol will lead to an improved outcome in acute severe UC.